Larvicidal Activities of the Extract and fractions of Paullinia pinnata Linn leaf - AA, Fred-Jaiyesimi; O, Anthony (Pharmacognosy Communications)
Background and objectives: The use of plants and their extracts in vector control for malaria has received recent attention. Paullinia pinnata leaf is used in folklore medicine for the treatment of fever and was investigated in this study for its larvicidal activity. Materials and methods: Effects of the methanol extract, pet. ether and chloroform fractions of P. pinnata leaf was been investigated against the third and fourth instar larvae of Anopheles gambiae by adopting the WHO method with little modification. Result: All the tested extract and fractions exhibited significant larvicidal effects against A. gambiae larvae. The pet. ether displayed the strongest response after 24 hr exposure, while the methanol extract exhibited a dose-dependent effect 48 hr after exposure. The Phytochemical analysis of P. pinnata revealed the presence of alkaloids, tannins, saponins. Discussion and Conclusion: This study indicates that P. pinnata leaf possesses larvicidal activity against Anopheles gambiae and may be a possible source for control of mosquito vectors.
Keywords: Paullinia pinnata; larvicidal activity; Anopheles gambiae; malaria